2017
DOI: 10.1123/japa.2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Regular Latin Dancing and Health Education May Improve Cognition of Late Middle-Aged and Older Latinos

Abstract: Disparities exist between Latinos and non-Latino whites in cognitive function. Dance is culturally appropriate and challenges individuals physically and cognitively, yet the impact of regular dancing on cognitive function in older Latinos has not been examined. A two-group pilot trial was employed among inactive, older Latinos. Participants (N = 57) participated in the BAILAMOS© dance program or a health education program. Cognitive test scores were converted to z-scores and measures of global cognition and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…Aguiñaga et al (2018) found that through 16 weeks of Latin dance training, people's physical activity level, fitness level, and EF can be improved. In addition, Latin dance training is also conducive to improving the overall cognitive ability of individuals (including EF, situational memory, WM) (Marquez et al, 2017). Zumba is a kind of sports project based on aerobic exercise, which integrates Cha Cha dance, Salsa dance, and other South American dance forms.…”
Section: Impact On Human Psychological Developmentmentioning
confidence: 99%
“…Aguiñaga et al (2018) found that through 16 weeks of Latin dance training, people's physical activity level, fitness level, and EF can be improved. In addition, Latin dance training is also conducive to improving the overall cognitive ability of individuals (including EF, situational memory, WM) (Marquez et al, 2017). Zumba is a kind of sports project based on aerobic exercise, which integrates Cha Cha dance, Salsa dance, and other South American dance forms.…”
Section: Impact On Human Psychological Developmentmentioning
confidence: 99%
“…Traditionally, the aim of dual-task training might focus on interference effects (Al-Yahya et al, 2011 ) and improving physical outcomes (e.g., decreasing falls) for impaired individuals (e.g., post-stroke), especially while managing dual tasks. More recently, studies have examined cognitive outcomes in dual tasks wherein there is more naturalistic interactivity (as in the cybercycle scenario above; Anderson-Hanley et al, 2012 ; as well as other interactive modalities such as dance: Foster, 2013 ; Kattenstroth et al, 2013 ; Dhami et al, 2015 ; Schoene et al, 2015 ; Burzynska et al, 2017 ; Marquez et al, 2017 ; Müller et al, 2017 ; Rehfeld et al, 2017 ). These recent studies seem to be converging on a similar cognitive-enhancing phenomenon that lends empirical support to the synergistic hypothesis outlined above and in part, elsewhere (Fissler et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that there might be positive effects of physical exercise on cognitive functions, particularly on attention, verbal memory and episodic memory [53][54][55][56], regardless of the intervention and control groups. Only Maass et al [57] demonstrated no significant relationship between physical activity and cognitive functions.…”
Section: Discussionmentioning
confidence: 84%
“…Four were randomized controlled studies [14,[53][54][55] and four were non-randomized controlled studies [13,[56][57][58]. Five studies originated on the American continent [13,14,53,55,56] and three studies were of German origin [54,57,58]. The main purpose of these studies was to explore the effect of a physical activity (particularly aerobic exercises, dancing, exergames, and cybercycling) on cognitive functions among the healthy elderly.…”
mentioning
confidence: 99%
See 1 more Smart Citation